2016
DOI: 10.1016/j.ijpharm.2016.01.083
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as a non-viral co-transfection system in a cystic fibrosis cell line

Abstract: Successful gene therapy requires the development of suitable vehicles for the selective and efficient delivery of genes to specific target cells at the expense of minimal toxicity. In this work, we investigated a non-viral gene delivery system based on chitosan (CS) to specifically address cystic fibrosis (CF). Thus, electrostatic self-assembled CS-pEGFP and CS-pEGFPsiRNA complexes were prepared from high-pure fully characterized CS (Mw ~20 kDa and degree of acetylation ~30%). The average diameter of positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
9
19
1
Order By: Relevance
“…Results revealed that the nucleic acid was retained in the gel pocket by CS with advanced efficiency in higher P/N charge ratios (Figure 4). The findings of the strong binding efficiency of nucleic acids and CS correspond to previous reports [23,33]. Deng et al even demonstrated protection of plasmid DNA from DNases by complexation with CS and hyaluronic acid [34].…”
Section: Salt Benefits the Formation Of Cs-aso Nanocomplexessupporting
confidence: 88%
See 3 more Smart Citations
“…Results revealed that the nucleic acid was retained in the gel pocket by CS with advanced efficiency in higher P/N charge ratios (Figure 4). The findings of the strong binding efficiency of nucleic acids and CS correspond to previous reports [23,33]. Deng et al even demonstrated protection of plasmid DNA from DNases by complexation with CS and hyaluronic acid [34].…”
Section: Salt Benefits the Formation Of Cs-aso Nanocomplexessupporting
confidence: 88%
“…The increase in zeta potential with increasing P/N charge ratio indicates that nanocomplexes were successfully formed, as the positive charge arises from the protonated amino groups that were not neutralized by the negatively charged phosphate groups of the ASO. With increasing P/N charge ratio, the amount of CS is increased and therefore an increasing excess of positively charged amino groups leads to an increasing zeta potential as shown in previous studies [23,30]. Furthermore, it was observed that nanocomplexes prepared with NaCl had a slightly lower zeta potential.…”
Section: Salt Benefits the Formation Of Cs-aso Nanocomplexessupporting
confidence: 52%
See 2 more Smart Citations
“…RNAi, a potent and highly specific gene-silencing phenomenon triggered by double-stranded RNA helix, 1 has emerged as a promising strategy for treatment of a wide range of diseases 2 . Small interfering RNA (siRNA) with 21–23 base pairs has been proven to be more efficient in gene silencing than other RNAi molecules and opens wide perspectives in therapeutics for the treatment of many diseases linked to elevated expression of identified genes, including cancer and infectious, inflammatory, and neurodegenerative diseases 3, 4.…”
Section: Introductionmentioning
confidence: 99%